Mechanical and Thermal Properties of Geopolymer Foams (GFs) Doped with By-Products of the Secondary Aluminum Industry - Ercoli, Roberto; Laskowska, Dorota; Nguyen, Van Vu; Le, Van Su; Louda, Petr; Łoś, Piotr; Ciemnicka, Justyna; Prałat, Karol; Renzulli, Alberto; Paris, Eleonora; Basilici, Matteo; Rapiejko, Cezary; et al. (Polymers, 2022)
The article deals with the investigation of geopolymer foams (GFs) synthesized using by-products coming from the (i) screening-, (iv) pyrolysis-, (iii) dust abatement- and (iv) fusion-processes of the secondary aluminum industry. Based on principles of the circular economy to produce new technological materials, the experimental study involves industrial by-products management through the recovery, chemical neutralization, and incorporation of these relatively hazardous waste into the GFs. The geopolymeric matrix, consisting of metakaolin (MK) and silica sand (SA) with a 1:1 wt.% ratio, and chopped carbon fibers (CFs, 1 wt.% MK), was doped with the addition of different aluminum-rich industrial by-products with a percentage from 1 to 10 wt.% MK. The gas (mainly hydrogen) produced during the chemical neutralization of the by-products represents the foaming agents trapped in the geopolymeric structure. Several experimental tests were carried out to characterize the mechanical (flexural, compressive, and Charpy impact strengths) and thermal properties (thermal conductivity, and diffusivity, and specific heat) of the GFs. Results identify GFs with good mechanical and thermal insulation properties, encouraging future researchers to find the best combination (for types and proportions) of the different by-products of the secondary aluminum industry to produce lightweight geopolymer foams. The reuse of these industrial by-products, which according to European Regulations cannot be disposed of in the landfill, also brings together environmental sustainability and safe management of hazardous material in workplaces addressed to the development of new materials.
Keywords: secondary aluminum; hydrogen; geopolymer foam; by-products recycling